A critical analysis and debate on the origins of the Lingbao fast. Issue 3 (3rd July 2022) - Lü, Pengzhi
ABSTRACT: According to the author's previous studies, the Daoist Lingbao fast, which appeared around 400, is a collective ritual that has the rite of Walking the Way as its core and that requires participants to observe a series of rules much like those of Buddhism. Building on the Sinified uposatha of Indian Buddhism, in combination with the Daoist rituals of the Heavenly Masters and the fangshi tradition, this ritual was created by the ancient Lingbao scriptures. However, in his recent work Han Jin daojiao yishi yu gu Lingbao jing yanjiu, Wang Chengwen holds an exactly opposite view of the origins of this ritual. He insists that the periodic fasts or the Lingbao fast derives from native Chinese religion, and that the periodic fasts in Chinese Buddhism imitate the latter. This article critiques Wang's view from three angles with a large amount of textual evidence, aiming at developing the study on the Buddho-Daoist interaction in medieval China.